Analisis Faktor Lingkungan Bisnis Ritel Berbasis Swalayan Pada Lab. Bisnis - Mukaram; Ira Siti Sarah (Jurnal Riset Bisnis dan Investasi, 2016)
Department of Business Administration has a business laboratory (Business Lab) that is based on the retail business concept. Until now, the profit per year earned by the Business Lab is still below the average of other retail store business in the same industry. The condition is suspected by less attention to stores environmental factors that have an impact on customer satisfaction. Competition among retail companies increasingly stringent push the owner to be more creative and innovative in creating marketing strategies. The retail business environment is one of the most important variables to be considered for the survival of a retail store. By knowing the dominant factors in the retail store environment variable, store management can make more appropriate marketing strategies to attract customers and increase customers satisfaction. This study aims to assess the environmental factors stores in Business Lab. The data collection is done by distributing 161 questionnaires to consumers of Business Lab. Data were analyzed using exploratory factor analysis (EFA). The result indicates there are three factors in the store's environment factors that need redefinition. First, the second factor was suggested to be renamed to promotions and convenience shopping after getting two new variables, namely direction and facilities. Secondly, the fourth factor is suggested to adjust its name to 'availability' as it contains two components, location and time of operation in the same factor. Third, the 'atmosphere of the shop' is divided into two different factors, namely 'convenience shopping' and 'storefront'.